The Effect of Social Media on the Spelling Ability of Students: A Case Study of Federal College of Education (FCE) Yola - Wilson, Fredrick (Edelweiss Applied Science and Technology, 2018)
This research investigates social media effect on the spelling abilities of students of Federal College of Education Yola. The study is significant because it helped in unveiling the negative effect of social media on students spelling abilities. The intents of the study are to examine the effect of social media on the student‟s spelling ability, to find out the nature of effect social media have on students spelling ability, to determine the number of hours spent by students on social networking activities every day and to determine how social media usage has affected students spelling ability. The social learning theory was adopted as the theoretical framework. Survey was the research method used, using questionnaire as the instrument which was conveniently and accidentally distributed among respondents in the levels. The study established that virtual platforms (social media) have negative effects on the spelling ability of students. Students expend excessive period on social media events than their academics especially the effect on the spelling ability of students during examination, when writing letters and using social media platform such as Whatsapp, Twitter and Facebook. The research generalized that the usage of social media by students affects their spelling ability negatively more especially when writing examination and letters, which in turn affects conventional way of writing. The study however recommends that more time should be channeled and spent on productive academic engagement and institutions should come up with ways of harnessing such virtual platforms academically in order to enhance students spelling ability since they are so addicted to social media.